MODIFIKASI PATI HANJELI (Coix lacryma-jobi L.) BERPORI MELALUI ULTRASONIKASI DAN OZONASI - Subroto, Edy; Indiarto, Rossi; Wulandari, Endah; Astari, Astri Puji (Universitas Sebelas Maret (UNS), 2021)
Adlay (Coix lacryma-jobi L.) is a potential source of starch but has not been utilized optimally. Native adlay starch has several weaknesses such as functional properties of low swelling volume and solubility, prone to retrogradation, and low stability. Physical modification of ultrasonication and chemical modification by oxidation using ozone can be an alternative to improve the functional properties of adlay starch through the formation of porous starch. The aim of this research was to produce porous adlay starch by ultrasonication and ozonation. The study consisted of several different treatments on hanjeli starch (ozonation starch, ultrasonication of 15 minutes, ultrasonication of 30 minutes, combined ultrasonication of 15 minutes and 30 minutes with ozonation). The results showed the appearance of pores on the surface of the granules of modified adlay starch with the best results being modified combination of ultrasonication 30 minutes and ozonation, which resulted in a decrease in swelling volume from 18.13 ± 3.98 mL/g to 15.71 ± 0.35 mL/g, an increase in solubility from 6.76 ± 0.62% to 9.59 ± 0.44%, and a decrease in water absorption capacity from 1.25 ± 0.02 g/g to 1.13 ± 0.02 g/ g. Modification of adlay starch by ultrasonication, ozonation, and their combination effectively produced porous starch granules, but did not cause the formation of new functional groups in starch.